Restoration and Reinforcement of Stone Buildings and Brick Walls‏:‏‎ ‎Review paper (Journal of University of Babylon for Engineering Sciences, 2025)
The art of maintaining our cultural legacy through architecture is known as restoration. It is the process of restoring historic structures that have lost a large amount of their aesthetic value due to deterioration and cracking caused by time, natural disasters, and other factors.Finding engineering solutions to fix cracks and damage in brick walls is necessary to reduce material loss rather than demolishing buildings or preserving historical or archaeological significance because stone buildings and brick walls sustain significant material damage from weather, time, seismic movements, and other factors.In general, restoration seeks to sustain the buildings through engineering and documentation while maintaining the structural integrity of the structures to be repaired. More than just a building or institution, preserving architectural history and emphasizing its worth has become crucial to urban growth. It maintains the character of the location and the structure and forges enduring ties between succeeding generations. Heritage and historically significant structures that represent the nation's age and civilization are being protected more and more these days. There are numerous engineering and scientific ways to address these damages, enhance the walls, and increase the longevity of brick-built structures and walls.